Ammonium oxidation activity promotes stable nitritation and granulation of ammonium oxidizing bacteria. (February 2022) - Juan-Díaz, Xènia; Carrera, Julián; Pérez, Julio
Abstract: Two-stage partial nitritation/anammox (PN/AMX) processes have been pointed out as a feasible configuration for achieving mainstream anammox. For two-stage configurations, stable partial nitritation has been reported feasible in granular sludge reactors. This study aimed to explore the operating conditions involved in the development of an autotrophic aerobic granular sludge using floccular sludge as inoculum. The influence of different parameters such as free ammonia concentration, settling time, superficial gas flow velocity and ammonium oxidation rate was investigated. Enhancing ammonium oxidation activity since the early phase of the operation (i.e. using conventional activated sludge as inoculum enriched with a fraction of a floccular nitrifying biomass) promoted a fast development (ca. 30 days) of an autotrophic aerobic granular sludge performing stable nitritation. When the seeded sludge presented a low nitrifying activity (lower than 0.1 g N L −1 d −1 ), the increase of the air-flow rate triggered the formation of an autotrophic aerobic granular sludge since ammonium oxidation activity was promoted. Contrarily, imposing low settling times (10 min) or strong free ammonia inhibitory conditions (FA concentrations higher than 50 mg N L −1 ) were shown to negatively influence the achievement of high ammonium oxidation rates, hampering the development of an autotrophic aerobic granular sludge. This study demonstrated the importance of ensuring high ammonium oxidation rates (higher than 0.2 g N L −1 d −1 ) for the proper development of an autotrophic partial nitritation granular sludge. Graphical abstract: Unlabelled Image Highlights: A stable nitritation granular sludge can be achieved from activated sludge. Ammonium oxidation activity induces nitritation granular sludge development. Boosting air flow rate enhances autotrophic aerobic granular sludge formation. Settling time reduction does not promote autotrophic aerobic granulation. Strong free ammonia conditions negatively affect ammonium oxidation activity.